Students' attitudes, self-efficacy and experiences in a modified Process-Oriented Guided Inquiry Learning undergraduate chemistry classroom - Vishnumolakala, Venkat Rao; Southam, Daniel; Treagust, David; Mocerino, Mauro; Qureshi, S. (R S C Publications, 2017)
This one-semester, mixed methods study underpinning social cognition and theory of planned behaviour investigated the attitudes, self-efficacy, and experiences of 559 first year undergraduate chemistry students from two cohorts in modified process-oriented guided inquiry learning (POGIL) classes. Versions of attitude toward the study of chemistry (ASCI v2), and chemistry attitudes and experiences questionnaire (CAEQ) were adopted, modified, and administered to understand and gauge students’ affective outcomes before (pre) and after (post) POGIL intervention. Students’ post-POGIL perceptions of their attitudes, self-efficacy and experiences were statistically significantly higher. In addition to confirmatory testing of reliability of data obtained from ASCI v2 and CAEQ in an Australian POGIL context, the findings suggest that POGIL intervention provides positive affective experiences to students who are new to chemistry or have limited prior chemistry knowledge.